Research progress of biomass fuel upgrading and distributed utilization technology. Issue 2 (February 2019) - Liu, Shuguang; Gao, Yage; Wang, Liang; Xu, Bowen; Deng, Min
Abstract: The study, development and application of biomass energy and alternative petroleum products are effective ways to ensure energy provision, reduce the dependence on fossil energy and resolve the future energy problems. The characteristics of biomass fuel were analyzed, and the upgrading methods of biomass fuels were discussed. Furthermore, the recent technologies of biomass conversion and utilization inland and abroad are reviewed from aspects of direct combustion, biochemical conversion (fermentation and anaerobic digestion), thermal chemical conversion technology (gasification, pyrolysis), liquefaction, compact molding, and supercritical fluid conversion. The application of biomass conversion technologies is presented including biomass gasification to generate electricity, gasification to produce hydrogen, thermal cracking to produce hydrogen, fermentation to produce fuel ethanol, thermal cracking to produce bio-oil, compact molding to produce solid fuel, fermentation of compost to produce fertilizer, anaerobic digestion to produce biogas, catalytic cracking to produce biofuel, and so on. Finally, the development of biomass energy distributed utilization technology is prospected.